PENAMBAHAN KAPUR TOHOR (CaO) PADA MEDIA PEMELIHARAAN UNTUK MENINGKATKAN PERTUMBUHAN LOBSTER AIR TAWAR (Cherax quadricarinatus) - Anton Aldino Trijaway; Achmad Noerkhaerin Putra; Mustahal Mustahal (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2023)
Molting is the most crucial phase in the development and growth of crayfish. The purpose of this study was to evaluate the effect of increasing the dose of CaO in the rearing medium on the growth and survival rate of crayfish (C.quadricarinatus). The freshwater crayfish used had an average weight of 4.85 ± 0.86 g and a length of 3.17 ± 0.15 cm. Lobsters were reared in an aquarium (60x30x40 cm) filled with 15 units with density of 20 liters. The study was experimental in nature with data analysis in the form of a completely randomized design (CRD) with 4 treatments and 3 replications, namely 0 mg/L (P0) treatment, 5 mg/L (P1) treatment, 15 mg treatment /L (P2), 30 mg/L (P3) treatment. The results showed that the weight SGR value in treatment P0 was 0.005 %.g/day, P1 was 0.011 %.g/day, P2 was 0.001 %.g/day, and T3 was 0.001 %.g/day. While the long SGR value in treatment P0 was 0.017 %.cm/day, P1 was 0.015 %.cm/day, P2 was 0.02 %.cm/day and P3 was 0.015 %.cm/day. The addition of lime at different doses (0, 5, 15 and 30 mg/L) in the rearing medium had no effect on growth, chemical composition, calcium content and water quality of crayfish.